Randomized Double-Blind, Placebo-Controlled Feasibility Study, Evaluating the Efficacy of Homeopathic Medicines in the Prevention of COVID-19 in a Quarantined Population - Talele, Gitanjali; Vaidhya, Shashikant; Chowdhary, Abhay; Herscu, Paul; Shah, Rajesh (Homeopathy, 2021)
Introduction Exploring preventive therapeutic measures has been among the biggest challenges during the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We explored the feasibility and methods of recruitment, retention, and potential signal of efficacy, of selected homeopathic medicines as preventive measure for developing COVID-19 in a multi-group study.Methods A six-group, randomized, double-blind, placebo-controlled prophylaxis study was conducted in a COVID-19 exposed population in a quarantine facility in Mumbai, India. Each group received one of the following: Arsenicum album 30c, Bryonia alba 30c, a combination (Arsenicum album 30c, Bryonia alba 30c, Gelsemium sempervirens 30c, and Influenzinum 30c), coronavirus nosode CVN01 30c, Camphora 1M, or placebo. Six pills twice a day were administered for 3 days. The primary outcome measure used was testing recruitment and retention in this quarantined setting. Secondary outcomes were numbers testing positive for COVID-19 after developing symptoms of illness, number of subjects hospitalized, and days to recovery.Results Good rates of recruitment and retention were achieved. Of 4,497 quarantined individuals, 2,343 sought enrollment, with 2,294 enrolled and 2,233 completing the trial (49.7% recruitment, 97.3% retention). Subjects who were randomized to either Bryonia alba or to the CVN01 nosode signaled (p <0.10) a lower incidence of laboratory-confirmed COVID-19 and a shorter period of illness, with evidence of fewer hospitalizations, than those taking placebo. The three other groups did not show signals of efficacy.Conclusion This pilot study supports the feasibility of a larger randomized, double-blind, placebo-controlled trial. Bryonia alba 30c and CVN01 30c should both be explored in disease prevention or shortening the course of disease symptomatology in a COVID-19-exposed population.
Keywords: coronavirus; SARS-Cov-2; preventive; COVID-19; nosode; potentization; homeopathy